The Effect of Ownership and Competitive Pressure on Firm Performance in Transition Countries. Micro Evidence from Bulgaria, Romania and Poland - Saul Estrin; Jozef Konings; Zbigniew Zolkiewski; Manuela Angelucci (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2001)
This paper uses a unique representative firm level data set to analyse the effect of domestic and international competitive pressure and ownership changes in three emerging economies, Bulgaria Poland and Romania. Our main findings can be summarized as follows: Domestic competitive pressure, measured by market structure, and increased import penetration are associated with higher firm perfirmance in Poland irrespective of the ownership structure of firms. Furthfirmore the positive effects of increased import competition are reinforced for foreign owned firms. In contrast, in Bulgaria and Romania, increased import penetration is associated with lower firm perfirmance, while there is some evidence that more competitive market structures is associated with higher total factor productivity. However, these effects depend on the ownership structure of firms, which suggests the existence of complementarities between competitive pressure and ownership changes. The results also indicate that privatisation has positive effects on firm perfirmance. In particular, domestic private firms and foreign owned firms outperfirm state owned firms. Furthfirmore, there is evidence that foreign owned firms do better than domestically owned private firms especially in Bulgaria and Poland. The results on ownership are somewhat weaker for Romania.
Keywords: D24; D40; D42; J42; L10; L33; P23; P31; 330; competitive pressure; privatisation; firm performance; Internationaler Wettbewerb; Wettbewerb; Privatisierung; Unternehmenserfolg; Bulgarien; Polen; Rumänien